Development of computer-based interactive multimedia : study on learning in elementary education - Rachmadtullah, Reza; MS, Zulela; Syarif Sumantri, Mohamad (International Journal of Engineering and Technology, 2018)
Computer-based learning media is the use of a computer to help present learning materials to students, monitor the progress of learning or choose additional learning materials in accordance with student learning needs individually or is a form of application and use of computers that are applied in student learning directly to convey the content of the lesson, providing student learning exercises. The purpose of this study is the development of interactive multimedia computer-based on the subject of civic education in elementary education. This research method using an approach of research and development with stages: requirement analysis, design, and validation expert. The results of this study found that interactive multimedia applications based on computer valid and suitable for use in teaching and learning activities in primary schools.Â Â